The Concept of Calculating Air Transportation Tariffs for Fuel Using the Fuel Aircraft Transportation Tariff Formula for Fuel Distribution to 3T Regions (Underdeveloped, Frontier, and Outermost Areas) - Lutfi Bahroni; Alvian Pratama; Very Aryanto; Ahmad Ubaidillah Maksum; Rachman Agung Siswanto (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
The one-price BBM (Fuel Oil) policy in the Papua region, launched by the Government of Indonesia, represents an effort to realize social justice for all Indonesian people. The government has tasked PT Pertamina with immediately implementing one-price fuel in the Papua region and 3T (Daerah Tertinggal, Terdepan, dan Terluar; Disadvantaged, Frontier, and Outermost) regions. This policy is expected to foster economic growth and development in Papua. However, distributing fuel to remote areas in Papua faces enormous challenges due to limited infrastructure, difficult geographical conditions, extreme weather, and security risks. Air transportation is the only effective mode for fuel distribution to these regions, though it incurs high logistics costs and significant operational complexity. In this study, The Concept of Calculating Air Transportation Tariffs for Fuel Using the Fuel Aircraft Transportation Tariff Formula for Fuel Distribution to 3T Regions (Underdeveloped, Frontier, and Outermost Areas) was developed by integrating a cost-based analysis approach with the Cash-Related Aircraft Operating Cost (CAROC) model, relevant laws and regulations, government policies, Pertamina and Oil and Gas guidelines, and field best practices. This Tariff Formula enables transparent tariff calculations based on key cost components, including aircraft leasing, fuel, maintenance, handling, insurance, and labor. The results provide an objective basis for establishing air transportation tariffs for fuel in areas with limited infrastructure and extreme operational conditions, such as Papua